High levels of resistance to nucleoside/nucleotide reverse transcriptase inhibitors in newly diagnosed antiretroviral treatment-naive children in sub-Saharan Africa. (1st August 2020) - Inzaule, Seth C.; Jordan, Michael R.; Bello, George; Wadonda-Kabondo, Nellie; Mounerou, Salou; Mbulli, Innocent A.; Akanmu, Sulaimon A.; Vubil, Adolfo; Hunt, Gillian; Kaleebu, Pontiano; Mthethwa-Hleza, Simangele; Dzangare, Janet; et al.
Abstract : N/A: Exposure of infants to antiretroviral drugs for prevention of mother-to-child transmission can induce resistance to nucleoside/nucleotide reverse transcriptase inhibitors (NRTIs). Data from nine national surveys of pretreatment drug resistance in children newly diagnosed with HIV show high levels of resistance to NRTIs included in first-line antiretroviral treatment (ART) regimens (dual abacavir-lamivudine/emtricitabine resistance). Additional research is needed to determine the impact of NRTI resistance on treatment response and optimize infant ART.